Міста Правобережної України кінця ХVІІІ – початку ХХ ст.: сучасний стан досліджень та перспективи вивчення - Прищепа, Олена; Pryshchepa, Olena (My University, 2013)
У статті з’ясовуються основні результати досліджень міст Правобережної України (кінець ХVІІІ – початок ХХ ст.) у вітчизняній історіографії в період незалежної України. Робиться висновок про домінування краєзнавчих підходів у їх висвітленні. Підкреслюються здобутки в дослідженні міст Волині. Наголошується на перспективах містознавчих студій, зокрема вивченні міського освітньо-культурного середовища.The article examines the main findings of research on town settlements of the Right-Bank Ukraine (the end of the 18th - the beginning of the 20th c.) undertaken during the times of independent Ukraine. The article reports that Ukrainian researchers, similarly to the previous, i. e. soviet, period, continued focusing on researching of economic, demographical, ethnical aspects of towns development of the Right-Bank Ukraine as well as of activities of town self-governance. The conclusion is drawn about the domination of local lore approaches in the analysis of towns. Results of the research on Volyn towns are highlighted. The emphasis is made on the perspective of urban studies, in particular of educational-cultural environment of the towns.
The Towns of the Right-Bank Ukraine at the End of the 18th – the Beginning of the 20th cc.: Current State of Research and Perspectives for Further Investigations
Keywords: міста; Правобережна Україна; Російська імперія; напрями досліджень; освітньо-культурне середовище; towns; Right-Bank Ukraine; Russian Empire; research directions; educational-cultural environment